Avelumab as second-line therapy for metastatic, platinum-treated urothelial carcinoma in the phase Ib JAVELIN Solid Tumor study: 2-year updated efficacy and safety analysis. Issue 2 (9th October 2020) - Apolo, Andrea B; Ellerton, John A; Infante, Jeffrey R; Agrawal, Manish; Gordon, Michael S; Aljumaily, Raid; Gourdin, Theodore; Dirix, Luc; Lee, Keun-Wook; Taylor, Matthew H; Schöffski, Patrick; Wang, Ding; et al.
Abstract : Background: Anti-programmed cell death ligand 1 (PD-L1)/programmed cell death 1 antibodies have shown clinical activity in platinum-treated metastatic urothelial carcinoma, resulting in regulatory approval of several agents, including avelumab (anti-PD-L1). We report ≥2-year follow-up data for avelumab treatment and exploratory subgroup analyses in patients with urothelial carcinoma. Methods: Patients with previously treated advanced/metastatic urothelial carcinoma, pooled from two cohorts of the phase Ib JAVELIN Solid Tumor trial, received avelumab 10 mg/kg every 2 weeks until disease progression, unacceptable toxicity or withdrawal. End points included best overall response and progression-free survival (PFS) per RECIST V.1.1, overall survival (OS) and safety. Post hoc analyses included objective response rates (ORRs) in subgroups defined by established high-risk/poor-prognosis characteristics and association between time to response and outcome. Results: 249 patients received avelumab; efficacy was assessed in 242 postplatinum patients. Median follow-up was 31.9 months (range 24–43), and median treatment duration was 2.8 months (range 0.5–42.8). The confirmed ORR was 16.5% (95% CI 12.1% to 21.8%; complete response in 4.1% and partial response in 12.4%). Median duration of response was 20.5 months (95% CI 9.7 months to not estimable). Median PFS was 1.6 months (95% CI 1.4 to 2.7 months) and the 12-month PFS rate was 16.8% (95% CI 11.9% to 22.4%). Median OS was 7.0 months (95% CI 5.9 to 8.5 months) and the 24-month OS rate was 20.1% (95% CI 15.2% to 25.4%). In post hoc exploratory analyses, avelumab showed antitumor activity in high-risk subgroups, including elderly patients and those with renal insufficiency or upper tract disease; ORRs were numerically lower in patients with liver metastases or low albumin levels. Objective response achieved by 3 months versus later was associated with longer OS (median not reached (95% CI 18.9 months to not estimable) vs 7.1 months (95% CI 5.2 to 9.0 months)). Safety findings were consistent with previously reported 6-month analyses. Conclusions: After ≥2 years of follow-up, avelumab showed prolonged efficacy and acceptable safety in patients with platinum-treated advanced/metastatic urothelial carcinoma, including high-risk subgroups. Survival appeared longer in patients who responded within 3 months. Long-term safety findings were consistent with earlier reports with avelumab treatment in this patient population.